Morphological study of synthesized RGO/ Pt nanocomposites via facile chemical reduction method - Mohamad Fahrul Radzi Hanifah; Juhana Jaafar; Madzlan Aziz; Mohd Hafiz Dzarfan Othman; Mukhlis A. Rahman; Ahmad Fauzi Ismail; Chiong, Sie Jing; Farhana Aziz; W.N.W. Salleh; N. Yusof; M.Z.A. Thirmizir (Penerbit Universiti Kebangsaan Malaysia, 2017)
Reduced graphene oxide nanosheet (RGO)/Pt nanocomposite have been successfully prepared through a facile chemical reduction method. The reduction of Pt precursor was carried out using sodium borohydride as the efficient chemical reductant. The morphology of RGO/Pt nanocomposite was investigated using high resolution transmission electron microscopy (HRTEM) and field emission scanning electron microscopy (FESEM). HRTEM analysis showed that platinum nanoparticles were homogenously distributed onto the surface of RGO. The electrochemical study proved that Pt nanoparticles were successfully incorporated onto RGO. Therefore, it can be concluded that the proposed method could provide well-dispersed of Pt nanoparticles onto RGO to form RGO/ Pt nanocomposite.